A simple hypothesis of executive function - Kopp, Bruno (Frontiers in Human Neuroscience, 2012)
Executive function is traditionally conceptualized as a set of abilities required to guide behavior toward goals. Here, an integrated theoretical framework for executive function is developed which has its roots in the notion of hierarchical mental models. Further following Duncan (2010a,b), executive function is construed as a hierarchical recursive system of test-operation-test-exit units (Miller et al., 1960). Importantly, it is shown that this framework can be used to model the main regional prefrontal syndromes, which are characterized by apathetic, disinhibited and dysexecutive cognition, and behavior, respectively. Implications of these considerations for the neuropsychological assessment of executive function are discussed.